O impacto socioespacial do Aeroporto Internacional Tancredo Neves no vetor norte da Região Metropolitana de Belo Horizonte - Bárbara Lúcia Pinheiro de Oliveira França (2014)
Nowadays the North Vector of the Metropolitan Region of Belo Horizonte undergoes several urban interventions promoted primarily by the State of Minas Gerais Government. Among the actions of urban planning logistical nature under implementation highlights the "Aerotrópole" Belo Horizonte, whose structuring center is the consolidation of the recently privatized, Tancredo Neves International Airport and its industry airport. In this context, the problematic that involves this study is inserted in an investigation about how the modifications of spatial infrastructure financed by the State impact and will change the (re)production of the metropolitan space. So, is elected as the main focus of research, the identification and reflection on how to give socio-spatial relations and contradictions of this new dynamics. Find up-to establish in different scales relations and connections between global factors/actors and places involved in the process with a view to understanding the spatial (re)production being consolidated. The new model of air and port of the Metropolitan Region of Belo Horizonte will be able to provide on the one hand, economic growth associated with the appropriation of space for playing the capital; and, on the other hand, the intensification of existing spatial contradictions, via deepening socio-spatial segregation, by homogenization, fragmentation and hierarchy of space, mainly generated by the articulation of different agents process. Furthermore, we seek to reflect about social and environmental consequences put by the large project "Aerotrópole" located on the APA Carste Lagoa Santa territory. As changes proposed by the new ventures are already producing changes in the geography of the North Vector, proposes a critical reflection that it becomes a contribution to advance the discussions about capitalist development with emphasis on the role of the state and the intrinsic contradictions of social reproduction in the metropolis. Public urban actions in metropolitan peripheries contribute to increase the value of the land in the intermediate spaces unoccupied by private property that revalue and become the object of interest of real estate agents. Thus it is considered that the reflection through the analysis of socio-spatial processes contribute to the ongoing critical thinking about capitalist urbanization.